Analysis Effectiveness of On-The-Job Training in Improving Performance of Marketing Division at Koja Trade Mall - S, Hafsah Tazkiya; Pangestu, Aria Bayu (Journal of Business and Management, 2020)
Abstract. Koja trade mall has experienced an insolvency phase that causes income decreased also impacted their paying ability of the employees that continuously affect the employee’s performance. Therefore, the company conducted on-the-job training to increase an employee’s performance which is coaching and job rotation for the marketing division. But the on-the-job training impact did not last long on the employee so it is considered as ineffective. Therefore, this research was to determine what factors that cause ineffective on-the-job training in marketing division of Koja Trade Mall. The results of on-the-job training effectiveness show that based on four-level of Kirkpatrick training effectiveness, there are some levels that not fulfill by the marketing division of Koja Trade Mall. The research recommended to use the external parties in conducting the speciality training for the employees to improve their knowledge.Keywords: marketing division, on-the-job, training, training effectiveness, Koja Trade Mall